Trait body image flexibility as a predictor of body image states in everyday life of young Australian women. (September 2019) - Tan, Weixi; Holt, Naomi; Krug, Isabel; Ling, Mathew; Klettke, Bianca; Linardon, Jake; Baxter, Kimberley; Hemmings, Shelley; Howard, Dominika; Hughes, Erin; Rivelli-Rojas, Isabella; Fuller-Tyszkiewicz, Matthew
Highlights: We asked whether body image in daily life differs for body image flexible individuals. More flexible individuals have lower average state body dissatisfaction and less variability. They are also less likely to engage in disordered eating behaviors linked to body dissatisfaction. There was mixed support for flexibility as a moderator of these state-based relationships. Abstract: The present study evaluated whether individuals with varying levels of trait body image flexibility differ in the severity, variability, and correlates of state body dissatisfaction experienced in their daily lives. One hundred and forty-seven women completed a baseline measure of trait body image flexibility, followed by a 7-day ecological momentary assessment phase in which participants self-reported state body dissatisfaction, disordered eating behavior, drive for thinness, and appearance comparisons at 10 semi-random intervals daily. Higher trait body image flexibility predicted lower average scores, less frequent reporting of high state body dissatisfaction, and less variability in their state body dissatisfaction ratings. Individuals with higher trait body image flexibility were also less likely to engage in a range of behaviors and cognitions previously shown to produce body dissatisfaction, including upward appearance comparisons, drive for thinness, binge eating, and dieting. However, few of these state-based relationships involving body dissatisfaction and these related behaviors and cognitions were moderated by trait body image flexibility. Overall, this pattern of findings suggests that body image flexible individuals may have less negative body image because they are less inclined to engage in behaviors and cognitions in their daily lives that encourage negative body image.